2011
DOI: 10.3762/bjnano.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of carbon nanomembranes from self-assembled monolayers

Abstract: SummaryThis paper reports on the mechanical characterization of carbon nanomembranes (CNMs) with a thickness of 1 nm that are fabricated by electron-induced crosslinking of aromatic self-assembled monolayers (SAMs). A novel type of in situ bulge test employing an atomic force microscope (AFM) is utilized to investigate their mechanical properties. A series of biphenyl-based molecules with different types of terminal and/or anchor groups were used to prepare the CNMs, such as 4'-[(3-trimethoxysilyl)propoxy]-[1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 26 publications
(36 reference statements)
2
52
0
Order By: Relevance
“…It should be made clear at this point that classical molecular dynamics cannot describe electronic properties or molecular orbitals, but structure in the sense of atomic positions and mechanical properties such as vibrational spectra or Young’s moduli [16]. …”
Section: Classical Carbon–carbon Interactionmentioning
confidence: 99%
“…It should be made clear at this point that classical molecular dynamics cannot describe electronic properties or molecular orbitals, but structure in the sense of atomic positions and mechanical properties such as vibrational spectra or Young’s moduli [16]. …”
Section: Classical Carbon–carbon Interactionmentioning
confidence: 99%
“…21 Apart from that the terminal functionality of CNMs is inherited from the precursor molecules but can be modified upon electron irradiation, e.g., nitro group converts to amino group, 22 which enables further molecular grafting onto aminoterminated regions. 23,24 Mechanical properties of CNMs have been characterized by bulge testing in an atomic force microscope (AFM bulge test) 25 and it was found that their Young's moduli can also be tailored in the range of 10-20 GPa, depending on the precursor molecules. 26 In contrast to graphene being a semimetal, the pristine CNMs are dielectric and structurally amorphous but can be converted to well-conducting nanocrystalline graphene upon thermal annealing.…”
mentioning
confidence: 99%
“…The boundaries are considered fixed and no delamination occurs during vibration, as verified elsewhere in the case of pressure loading in the bulge test. 25,26 The spatial part sin According to the Rayleigh-Ritz method, [30][31][32] the natural frequencies of a rectangular membrane with direction dependent tensions can be expressed as where q s is the area density and P x and P y depict the pretension in the x and y directions.…”
mentioning
confidence: 99%
“…Fig. The testing was performed by adjusting an AFM tip to the nano- membrane center, 35,36 as schematically shown in Fig. An orifice with the spanned C 60 -JNM is observed (marked "freestanding"), which indicates that the hybrid can support its own weight and preserve its mechanical integrity.…”
mentioning
confidence: 99%
“…3b and c) are observed, which are typical for mechanically robust nanosheets. By fitting multiple curves to a pressuredeflection equation for rectangular/square membranes, 35,36 Young's modulus (E Young ) can be extracted (Fig. 3d shows a homogeneous freestanding JNM/(C 60 -JNM) 3 heterostructure spanning over an orifice with dimensions of 40 × 44 μm 2 .…”
mentioning
confidence: 99%